Quality of life in families of persons with disability - Verdugo Alonso, Miguel Ángel; Córdoba Andrade, Leonor; Rodríguez Aguilella, Alba (Pensando Psicología, 2020)
Aim: To establish advances in the understanding of the quality of life in families of people with disabilities within the framework of family-centered attention.Methodology: From the relationships between family and disability from the model of quality of life, the main studies in Spain and Latin America are analyzed.Results: it is shown that, research on family quality of life has shown significant progress in the development of professional and organizational practices aimed at strengthening the autonomy of families for decision-making in the face of crucial aspects of their lives and; a strong interest in professionals and organizations to have quality tools of family life that assesses the impact of their practice and their services.Conclusion: The improvement in the quality of family life is fundamental in the personal development and social inclusion of people with disabilities.
Keywords: families; disability; quality of life; family quality of life; assessment